Employment aspects related to quality of life in North Macedonia - Lozanoska, Aleksandra; Djambaska, Elizabeta; Piperkova, Irina (Integrated Business Faculty, 2022)
The purpose of this article is to identify the aspects of employment in the Republic of North Macedonia in terms of the quality of life. Therefore, certain features of the quantity and quality of employment for the last ten years have been taken into account, covering the working age population aged 15 to 64, vis-a-vis EU-27 (excluding the United Kingdom). The analysis refers on data indicators about the quality of life provided by Eurostat. Employment, hence the possibility for productive activity and earning income, is prerequisite for better life quality. Also, the improvements in terms of higher wages, permanent job and јоb arrangements that correspond to the relevant education and skills are paramount for person’s life quality. The Covid-19 pandemic drastically changed everyday life and caused changes in work, so the perceptions of the employees in Macedonia on this issue, obtained as a result of an online survey, are also presented in this paper. The findings of the survey confirm that the pandemic caused changes in work, as well as job losses, but also other qualitative changes in employment, such as work from home, which significantly affect the quality of life. This research doesn’t cover all aspects of employment and unemployment in terms of quality of life. There are other relevant issues on this theme which can be topics for further studies and analysis.
Keywords: quality of life, employment rate, unemployment, income, skills mismatch, types of work